Frontier Warfare in the St Omer Chronicle - Rogers, Clifford J. (Military Cultures and Martial Enterprises in the Middle Ages. Essays in Honour of Richard P. Abels, 2020)
Keywords: Chronik; Hundertjähriger Krieg (1337–1453); Kriegführung; Saint-Omer

Mise en évidence d'une marche culturelle par le matériel figulin au Haut-Empire romain dans le Nord de la Gaule Belgique. La vallée de la Deûle - Herbin, Patrice; Loridant, Frédéric (Revue du Nord, 2003)
Abstract: „After the conquest, the influence of the Roman world varies according to the regions. The Deûle valley is situated in Gallia Belgica, at the confines of the cities of the Atrebates and of the Menapians. Potery kitchenware, fundamental implements of the household, artefact found in large amounts during archaeological excavations and above all a well-studied material reveals an area where « Gallo-Roman » potery is intimately mixed with native potery. Thus, for the Menapians, the eartheware keeps its native character (moulded potery) while among the Atrebates, the Morins and the Nervians, the inventories are altered in depth (potery shaped on the fast wheel) at the latest by the Flavian period. The lower Deûle valley does not constitute the only cultural « border ». This area of contact, this « culture frontier » is prolonged to the north, along the Lys valley, and to the east, along the Scheldt valley. Does it represent a resistance to Romanization as was occasionally hinted at, or the consequence of the minor strategic and economic interest for Rome of this region in the Higher Empire? The second hypothesis sounds more attractive because everything tends to show that, beside the resources in salt and taxes, echoed in the cadastral surveys, Rome was hardly concerned by this region situated so far apart which could thus, at least for some time (until the 70s) keep its cultural singularities.“
Keywords: Atrebaten; Belgen; Deûletal; Funde; Keramik; Kulturkontakt; Menapier; Nervier; Romanisierung; Römerzeit